Cultural Negotiation: NGO Strategies in Handling Sexual Violence in Islamic Boarding Schools - Desi Purnilasari; Ainun Fitri Mughiroh (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study addresses the critical issue of sexual violence within Islamic boarding schools in Jombang, a region recognized as the “City of Santri.” The research aims to analyze the public relations strategies employed by the Women’s Crisis Center (WCC) Jombang in navigating the complex socio-cultural landscape of these religious institutions to prevent and handle sexual abuse. Utilizing a qualitative descriptive approach with a case study design, data were gathered through in-depth interviews with WCC’s advocacy and counseling staff, as well as pesantren leaders, supplemented by documentation of strategic policies. The analysis is framed within the Relationship Management Theory, assessing dimensions of trust, commitment, satisfaction, and control mutuality. The findings reveal that WCC Jombang successfully implements a “cultural negotiation” model through theological framing, recontextualizing gender-based advocacy into Islamic principles such as Mubadalah and Maqashid Syariah. Furthermore, the establishment of participatory Standard Operating Procedures (SOP) demonstrates a transition from institutional resistance to collaborative partnership. This research contributes to Islamic communication studies by demonstrating how strategic communication can bridge universal human rights with local religious traditions. It emphasizes that effective advocacy in sensitive environments relies on trust-building, linguistic adaptation, and respect for hierarchical authorities.